2021
DOI: 10.1186/s42269-021-00628-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and ESBL production in Escherichia coli from various sources in Aba metropolis, Nigeria

Abstract: Background The increase in multidrug resistance (MDR) among pathogenic bacteria responsible for infectious diseases has led to lack of effectiveness of some antibiotics. The ability of Escherichia coli to harbor resistant genes has made the treatment of infections a major challenge. This study was carried out to assess antibiotic resistance and extended-spectrum beta-lactamase (ESBL) production of E. coli from various sources in Aba metropolis, Nigeria. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…The global incidence of ESBL-producing bacteria is on a rising trend ranging from 33 to 91% in reported cases [40][41][42][43]. Our study identified the presence of ESBL-producing MDR Aeromonas strains in the aquatic environment with fisheries operations posing a substantial public health risk.…”
Section: Discussionmentioning
confidence: 74%
“…The global incidence of ESBL-producing bacteria is on a rising trend ranging from 33 to 91% in reported cases [40][41][42][43]. Our study identified the presence of ESBL-producing MDR Aeromonas strains in the aquatic environment with fisheries operations posing a substantial public health risk.…”
Section: Discussionmentioning
confidence: 74%
“…Characteristic colonies were then purified and stored. Following this, DNA was obtained from pure cultures using the boiling method (Ajuga et al, 2021). In brief, pure cultures were emulsified in 100 µl volume of sterile DNase free distilled water.…”
Section: A Isolation and Identification Of Test Strainsmentioning
confidence: 99%
“…Antimicrobial susceptibility of the isolates was carried out using the modified Kirby-Bauer Disk Diffusion method [13]. Mueller Hinton (MH) Agar (Oxoid, UK) was prepared according to the manufacturer's instructions and 10ml transferred into 90 mm diameter sterile Petri dishes making a depth of 4 mm.…”
Section: Antimicrobial Susceptibility Testmentioning
confidence: 99%